Modeling the impact of interventions during an outbreak of HIV infection among people who inject drugs in 2012–2013 in Athens, Greece. (1st May 2022) - Flountzi, Eleni; Lim, Aaron G.; Vickerman, Peter; Paraskevis, Dimitrios; Psichogiou, Mina; Hatzakis, Angelos; Sypsa, Vana
Abstract: Background: A large HIV outbreak in People Who Inject Drugs (PWID) occurred in Athens, Greece in 2011–2013. In response, opioid substitution treatment (OST) and needle and syringe programs (NSP) were scaled-up and a seek-test-treat program was introduced in mid-2012. We aim to assess the impact of these interventions. Methods: A mathematical model of HIV transmission among PWID was calibrated to data available over time (2009–2013) on HIV prevalence, NSP/antiretroviral treatment (ART) coverage and high-risk injection. A combined interventions scenario, including decrease in high-risk injection through linkage to OST and modification of risk behaviours and access to NSP and ART, was compared to a counterfactual scenario (no improvement at the levels of these interventions), with HIV incidence being the main outcome. Results: HIV incidence increased from <0.1 new cases/100 person-years (in 2009) to 11.0 new cases/100 person-years (in 2012). Under both models, a subsequent decline was projected following early 2012, with incidence at the end of 2013 in the combined interventions scenario being lower by 77% compared to the counterfactual. The projected reduction in incidence under the intervention scenario was in agreement with empirical data. HIV prevalence would have escalated to 20.4% (95% CrI: 16.9%, 23.6%) in 2013 under the counterfactual scenario (vs. 16.8% (95% CrI: 11.2%, 23.0%) under the combined interventions scenario). In total, 31.4% of HIV cases (392) were averted over 2012–2013. Conclusion: These results underline the importance of high-coverage harm reduction programs and of community-based interventions to rapidly reach PWID most in need. Highlights: Multiple HIV outbreaks have been documented among PWID since 2010. A 150-fold increase in HIV incidence occurred over 2009–2012 among PWID in Athens. HIV incidence declined by 89% in two years as a result of multiple interventions. One third of HIV cases were averted over 2012–2013. High coverage harm reduction programs and community-based interventions are essential.